Cultural Differences in the Construal of Suffering and the COVID-19 Pandemic. Issue 6 (August 2021) - Ji, Li-Jun; Khei, Mark; Yap, Suhui; Wang, Xinqiang; Zhang, Zhiyong; Hou, Yubo
The present research examines how suffering is construed across cultures. Study 1 ( N 1 = 264; N 2 = 745) asked participants to provide free associations for suffering. Chinese individuals generated more positive associations than did Euro-Canadians. Study 2 ( N = 522) had participants create a hypothetical potion of suffering to represent what people would experience while suffering. Chinese participants added more positive ingredients and fewer negative ingredients than Euro-Canadians did. How would cultural differences in the construal of suffering matter in a real-life negative situation? Study 3 ( N = 608) showed that Chinese participants generated a greater proportion of potential positive outcomes for the COVID-19 outbreak and reported more positive affect during the pandemic than did Euro-Canadians. Thus, Chinese construe suffering more positively than Euro-Canadians. These findings are consistent with previous research on cultural differences in dialectical thinking and lay theory of change and have implications for coping and resilience.